Relasi Sufisme dengan Modernitas dalam Perspektif ‘Abd al-Ḥalîm Maḥmûd - Muhammad, Ahmad (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article discusses the theme of Sufism, modernity, and the relationship between the two. This study concludes that according to Mahmûd, Sufism can deliver the people towards the true knowledge. In order to obtain this knowledge, the method of ittibâ? to al-Qur?ân and Sunnah is used. The method is implemented through purification of the soul. This method differs from the two methods used in modernity, namely the Cartesian philosophical method and Baconian observation method. The last two methods are only able to produce empirical-rational knowledge. According to Mahmûd, both methods are only appropriate when used in the context of physical science, not of metaphysics and moral issues. The last two issues are more appropriate when viewed from the perspective of Sufism, which is guided by revelation. Mahmûd argued that the relationship between Sufism and modernity is a complementary relationship, in which each of the two aspects is a complementary entity to another. It means that modernity will be spiritually empty without Sufism on one hand and Sufism will also be more meaningful when supported by modern science on the other.